Preclinical evaluation of an endoscopic electroporation system - Forde, Patrick F.; Sadadcharam, Mira; Bourke, Michael G.; Conway, Thomas A.; Guerin, Shane R.; de Kruijf, Marcel; O’Sullivan, Gerald C.; Impellizeri, Joseph; Clover, Anthony J. P.; Soden, Declan M. (Endoscopy, 2016)
Background and study aims: Targeted delivery of specific chemotherapeutic drugs into tumors can be achieved by delivering electrical pulses directly to the tumor tissue. This causes a transient formation of pores in the cell membrane that enables passive diffusion of normally impermeant drugs. A novel device has been developed to enable the endoscopic delivery of this tumor permeabilizing treatment. The aim of the preclinical studies described here was to investigate the efficacy and safety of this nonthermal ablation system in the treatment of gastrointestinal cancer models.Methods: Murine, porcine, and canine gastrointestinal tumors and tissues were used to assess the efficacy and safety of electroporation delivered through the special device in combination with bleomycin. Tumor cell death, volume, and overall survival were recorded. Results: Murine tumors treated with electrochemotherapy showed excellent responses, with cell death being induced rapidly, mainly via an apoptotic-type mechanism. Use of the system in canine gastrointestinal cancers demonstrated successful local endoluminal tumor resolution, with no safety or adverse effects noted.Conclusions: Electroporation via the new device in combination with bleomycin offers a nonthermal tumor ablative approach, and presents clinicians with a new option for the management of gastrointestinal cancers.